AI-Based Transformer Matching Network Synthesis Using a Data-Efficient Two-Step Method - Simone, Gianluca; Tas, Deniz; Schneider, Fabian; Schilling, Raphael; Engelmann, Andre; Maiwald, Timo; Breun, Sascha; Hagelauer, Amelie; Franchi, Norman (RWW 2026, 2026)
This work presents an artificial intelligence-driven approach for automated on-chip impedance-matching (IM) transformer design, achieving layout generation within seconds. Unlike direct prediction approaches, where machine learning models directly estimate the optimal transformer geometry based on input and output impedances, this method follows a two-step process. This new approach significantly reduces the required training data for the neural network while maintaining high accuracy and efficiency. As a proof of concept, the synthesis of a D-band transformer in IHP’s SG13G2 technology is presented and optimized using the algorithm proposed in this paper. The approach is versatile and applicable across technologies, frequency ranges, and matching network structures, making it a scalable solution for automated IM desig
https://cris.fau.de/converis/publicweb/Publication/354267870
Keywords: artificial intelligence; design automation; matching network; neural network; radio frequency integrated circuit; transformer

Validation of an Open-Source RFIC Design Flow Using a 130 GHz Low-Noise Amplifier - Simone, Gianluca; Grund, Martin; Koch, Manuel; Breun, Sascha; Weigel, Robert; Franchi, Norman (2025 IEEE Asia-Pacific Microwave Conference (APMC), 2026)
This paper presents a complete open-source design and verification flow for analog and RF integrated circuits, applied to a 130 GHz low-noise amplifier (LNA). The circuit is implemented using the open-source SG13G2 PDK from IHP, based on a 130nm SiGe BiCMOS technology. The LNA uses a cascode topology with differential output and transformer-based matching. The full design flow includes schematic entry with Qucs-S, circuit-level analysis using Ngspice and Xyce, as well as layout generation in Klayout and electromagnetic simulation of passive structures with openEMS. Key performance metrics such as S-parameters, stability, noise figure, transient response, and output referred P1 dB are extracted and compared against commercial reference tools. The results show excellent agreement, validating the accuracy and practical usability of the proposed open-source flow for advanced high-frequency analog and radio frequency integrated circuit (RFIC) desig
https://cris.fau.de/converis/publicweb/Publication/354480979
Keywords: BiCMOS integrated circuits; Design flow; Klayout; Low-noise amplifiers; Millimeter wave integrated circuits; Ngspice; openEMS; Open-source; Qucs-S; Xyce